1227 Longterm Follow Up of Cognitive Function Children Born at the Limit of Viability After Active Perinatal Care, UmeÅ-Uppsala Study. (October 2012) - Karlsson, J; Hagglof, B; Farooqi, A
Abstract : Objective: To determine the nature of cognitive function, frequency and severity of cognitive deficit, in 10 to 15-year-old extremely preterm (EPT) children born at 2 tertiary care centers in Sweden adhering to a policy of universal resuscitation of all infants born alive. Methods: The outcomes of 121 surviving EPT children, born 1992–1998, were compared to a control group of 100 term children. Children were assessed with WISC- III at 9–16 years of age. Relationship of perinatal risk factors (PNRF) with the outcomes was examined with multivariate regression analyses (MRA). Results: The EPT group had a mean IQ of 80 (controls 103). 29% of the EPT children had an IQ below 70 (controls 3.4%), of which 9 % were under IQ 55 (controls 0). Another 30% of EPT children had IQ within the mildly delayed range, 70–84 (controls 12.6%). The preterm group has a greater variance between cognitive domains, with the language skills as relative strength and spatial thinking as pronounced weakness. MRA revealed that only gestaional age was inversely related to FSIQ (B 7.1, P 022) and Performance IQ (B 9.8, P<001). Conclusion: Cognitive dysfunctions remain high in EPT children. These numbers are similar to those from centres with less active perinatal care policies. Very few have severe cognitive impairment that curtail their activities in daily life.